Clinico sonological and laboratory co-relation with histopathology of acute appendicitis to develop new diagnostic scoring system (Yash scoring system) - Lamture, Yashwant R.; Ramteke, Harshal; Shinde, R. K.; Shahapurkar, Vinay V.; Gajbhiye, Varsha P. (International Surgery Journal, 2017)
Background: Of the many scoring systems currently available, the modified Alvarado scoring system (MASS) is the most widely employed, because of its ability to reduce negative appendectomy rate (NAR). Unfortunately, this system is more accurate in western population. In spite of the advances in the diagnostic and imaging techniques NAR have not decreased much. This clearly indicates the need of development of new diagnostic scoring system so we have developed new diagnostic scoring system (Yash Score). The objective of this study was to develop and study diagnostic accuracy of new diagnostic scoring system (Yash scoring system) for acute appendicitis. Methods: A prospective comparison YSS and MASS was done on 418 patients. Depending on clinical judgement appendicectomy was done. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy for YSS and MASS were calculated using SPSS 17.0 statistical software for statistical analysis and compared using Chi-square test. Results: The sensitivity and specificity of YSS was found to be 99.48 per cent and 92.86 percent respectively. The sensitivity and specify of MASS was 52.05 per cent and 100 per cent respectively. The positive predictive value and negative predictive value of YSS was 99.48 per cent and 92.86 per cent respectively. Negative and positive predictive values of MASS were 13.02% and 100% respectively. Conclusions: Comparison in between YSS and MASS in the present study shows significant statistical difference.